A decomposition framework for managing inventory and distribution of fluid products by an order-based-resupply methodology. (2nd November 2017) - Cóccola, Mariana E.; Méndez, Carlos A.; Dondo, Rodolfo G.
Highlights: The method provides a number of shifts to satisfy the demand of fluid products by customers while considering inventory constraints on plants. A decomposition method based on column generation is developed to solve the problem. Solutions to different examples, generated by using realistic data, are presented. Abstract: Fluid chemicals are usually distributed according two main methodologies; the vendor managed inventory modality and the order-based re-supply modality. In this paper, the problem of optimizing the delivery of fluids by tanker trucks on a daily basis according the order-basedresupply methodology is addressed. According to this modality, replenishment orders are triggered by customers specifying the quantity of fluids and time-windows within which the delivery must be fulfilled. The objective is to minimize the replenishment cost while meeting customers orders over the pre-defined time-horizon. An Integer Program modelling the problem is proposed and used to develop an incomplete branch & price procedure with the purpose of finding near optimal solutions to instances arising from realistic examples. A computational study on realistic examples with different topologies demonstrates that the method is effective and able to provide solutions with integrality gaps below the 16% threshold for instances with 120 orders.